PENGENALAN DAN PEMANFAATAN SOFTWARE SPSS DALAM PEMBELAJARAN STATISTIKA UNTUK MENINGKATKAN LITERASI DATA DAN KETERAMPILAN ANALISIS SISWA DI ERA DIGITAL - Sianturi, Rektor; Azarya N J Siahaan,; Vina Merina Br Sianipar,; Peniel Sam Putra Sitorus,; Eduward Situmorang,; Jaya Tata Hardinata, (Nusantara Hasana Journal, 2025)
In the digital era, the ability to understand and analyze data is very important for students. Statistics, a part of mathematics, is widely used in various fields, but its learning in schools is still often only theoretical and manual. SPSS is a data analysis software that can help students learn statistics in a more practical and interactive way. With SPSS, students can more easily understand concepts, hone analytical skills, and be ready to face the data-driven world of work. However, there are still many students who are not familiar with using SPSS due to lack of access and training. Therefore, this service aims to introduce and train students to use SPSS so that they are better prepared in the digital era. The method of this service activity is training by means of lectures to explain the basic concepts and introduction of SPSS, demonstrations to show how to use SPSS features and exercises so that participants can directly practice data processing with SPSS. SPSS is a software used to easily process and analyze statistical data. Data can be entered directly or copied from Excel into SPSS. Analysis is done through the menus, and results can be copied to Word, Excel, or PowerPoint for reports or presentations. One of the features of SPSS is Descriptive Statistics, which shows the minimum, maximum, mean and standard deviation of data. With SPSS, students can directly process and analyze data, making it easier to understand and present data correctly. Their analytical skills also improve, especially in using basic statistics to solve real problems. Learning with SPSS helps students better understand statistics and be ready to face the digital world that requires data analysis skills.